Remote Sensing Application for Assessing Salinity Intrusion in the Mekong Delta, Vietnam - Nguyen Thi Bich Phuong (Prince of Songkla University, 2020)
Thesis (M.Sc., Environmental Management Technology (International Program))--Prince of Songkla University, 2018